METHODS FOR EVALUATING THE USE OF DIFFERENT APPROACHES OF ORGANIZING THE PROCESS OF TEACHING STUDENTS - Ziborova, Viktorija; Kataļņikova, Sabina; Zagulova, Diana; Prokofjeva, Natalya (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Control over any process of human activity is carried out by evaluating its result. In the field of education, the goal is, as a rule, to check the effectiveness of one or another pedagogical approach to solving the set task. For this purpose, a pedagogical experiment is planned and carried out. First, the analysis of the problem is carried out and the participants of the experiment are determined, control and experimental groups of approximately equal number and level of preparedness are formed. Further, the researched pedagogical approach is implemented, the results obtained are studied and evaluated, and conclusions are drawn. Research was conducted at the Department of Software Engineering and involved its students, as well as teachers of Riga Technical University and Baltic International Academy.  Authors have studied the impact of introducing extended course content, interdisciplinary communications and feedback in teacher-student interaction. Computer training systems, a semantic network, and statistical analysis were used as assessment methods. Research aim of this article offers an overview of methods of assessing quality of education and their comparison in order to select the best one for conducting a pedagogical experiment, which were used in Riga Technical University.